قاعدة: ليس كل ما صحّ لغة يصحّ تفسيرا - دراسة نظرية تطبيقية - منصر, عباس (جامعة الوادي - University of Eloued, 2018)
يتناول البحث قاعدة تفسيرية لغوية أشار إليها غير واحد من المتقدمين والمتأخرين كابن جرير الطبري وأبي حيان الأندلسي وجمال الدين القاسمي والطاهر بن عاشور، كما أشار إليها غير واحد من علماء أصول التفسير كابن القيّم والشاطبي، إذ يخيّل إلى من لا دراية له بضوابط التفسير اللغوي أنّ اللغة أصل في تفسير القرآن الكريم بحكم نزوله بلسان العرب من جهة، وموافقة أساليبه أساليب العرب وأفانينهم في الخطاب من جهة ثانية، لذلك جانب الصواب من أخضع مفردات وتراكيب القرآن لمجرّد الاحتمال النحوي وما تمليه قواعد اللغة دون مراعاة لخصوصية النص القرآني وعرفه وظروف تنزيله. The research deals with a linguistic explanatory rule referred to by many earlier and later scholars, such as Ibn Jarir al-Tabari, Abu Hayyan al-Andalusi, Jamal al-Din al-Qasimi, and Muhammad al-Tahir ibn Ashur, as indicated by more than one of the scholars of Usul al-Tafsir, such as Ibn al-Qayyim and Imam al-Shatibi. Those who have no knowledge of the rules of linguistic interpretation may believe that the language is an origin in the interpretation of the Holy Qur’an by virtue of it being revealed in the language of the Arabs on the onehand, and its agreement with their methods of discourse on the other hand. and he agrees with their Styles of discourse on the second hand, A mistake may be made by those who subject the vocabulary and structures of the Qur’an to grammatical probability without taking into account the specificity of the Qur’anic text, its Styles and the circumstances of its descent.
مقال
Keywords: القاعدة؛ التفسير؛ المفردة القرآنية؛ المستوى النحوي؛ المستوى الأسلوبي; Rule; Interpretation; Quranic vocabulary; Grammar; Style